Mast cell‐deficient mice Mcpt5Cre/Dicer fl/fl redefine the role of mast cells in experimental bullous pemphigoid - S. Nsiah‐Dosu; C. Scholz; Z. Orinska; C. D. Sadik; R. J. Ludwig; E. Schmidt; D. Zillikens; K. Hartmann (Wiley, 2022)
Abstract Background Bullous pemphigoid (BP) is the most frequent autoimmune blistering disease of the skin affecting the elderly. BP is immunopathologically characterized by autoantibodies against BP180 and BP230. With the growing evidence of cell‐mediated autoimmunity in the pathogenesis of BP, it still remains unclear whether mast cells (MCs) are involved, due to conflicting data obtained from Kit‐dependent MC‐deficient mouse models. Objectives To clarify the role of MCs in experimental BP; the dynamics in cutaneous MC numbers, associated immune cells and the development of disease in Kit‐independent MC‐deficient mouse model. Methods Employing a recently established murine adult passive transfer model of BP induced by the transfer of pathogenic immunoglobulin G (IgG), lesional skin biopsies were investigated histologically and immunohistochemically for the time‐dependent MC accumulation and dermal infiltration. Results The numbers of cutaneous MCs increased following the induction of BP, in part, maintained by MC proliferation. Numbers of T cells, neutrophils and eosinophils in the skin also increased after BP induction, with eosinophils showing a preferential co‐localization with MCs. Furthermore, clinical disease manifestation in MC‐deficient Mcpt5Cre/Dicer fl/fl mice remained unchanged compared to MC‐sufficient Dicer fl/fl mice. The composition of the immune cell infiltration including as T cells, neutrophils and eosinophils was largely unaffected by the absence of MCs. Conclusion MCs do not play a pivotal role in the pathogenesis of passive IgG‐transfer mediated BP model. Their increase in number may be a bystander effect following tissue injury. We therefore suggest caution regarding the selection of MCs as sole targets for the development of novel drugs for BP.